The multifaceted effects of fluoxetine treatment on cognitive functions - Ampuero, Estíbaliz; Luarte, Alejandro; Flores, Francisca Sofia; Soto, Antonia Ignacia; Pino, Catalina; Silva, Viviana; Erlandsen, Macarena; Concha, Teresita; Wyneken, Ursula (Frontiers in Pharmacology, 2024)
Fluoxetine, the prototypical selective serotonin reuptake inhibitor (SSRI), is widely used to treat major depressive disorder (MDD) and a variety of other central nervous system conditions, primarily due to its established clinical safety profile. Although its efficacy in treating depression is wellrecognized, the impact of fluoxetine on cognitive functions remains inconsistent and elusive. In this review, we first examine the well-substantiated biological mechanisms underlying fluoxetine's antidepressant effects, which include serotonin reuptake inhibition and activation of TrkB receptorskey to brain-derived neurotrophic factor (BDNF) signaling. Subsequently, we delve into the cognitive side effects observed in both preclinical and clinical studies, affecting domains such as memory, attention, and executive functions. While certain studies indicate cognitive improvements in patients with underlying disorders, there is also evidence of negative effects, influenced by variables like gender, duration of treatment, age, disease pathology, and the specifics of cognitive testing.Significantly, the negative cognitive outcomes reported in preclinical research often involve healthy, non-diseased animals. This review underscores the necessity for heightened caution in fluoxetine prescription and further investigation into its potentially detrimental cognitive effects, even when used prophylactically.